Analisis Regresi Multivariate Berdasarkan Latar Belakang Santri - Pradana, Mohammad Syaiful; Nensi, Nur; Chandra, Novita Eka (Jurnal Matematika, 2023)
The students of the Matholiul Anwar Islamic boarding school come from various different regions so that they have quite diverse social and economic backgrounds. Likewise with learning motivation, achievement motivation and student learning achievement are also diverse. This study aims to determine the effect of the social and economic background of students on achievement motivation, learning motivation and learning achievement. The research sample used was 49 students in the F dormitory of the Matholiul Anwar Sukodadi Lamongan Islamic boarding school. This study uses the Multivariate Regression Analysis model. From the results of the partial study, the effect of social status on the dependent variable was concluded that there was an effect of social status on achievement motivation, learning motivation and learning achievement. Meanwhile, for the variable of economic status on the dependent variable, it can be concluded that there is no effect of economic status on achievement motivation, learning motivation, and learning achievement. Simultaneously, it was obtained that the background of the students affected the achievement motivation, learning motivation, and learning achievement in the F dormitory of the Matholiul Anwar Islamic boarding school.